Code detection of multilingual functionality in e-Commerce PHP website / Mohd Faizal Mohd Nor - Mohd Nor, Mohd Faizal (2006)
Web-based Information Systems such as e-commerce website has grown rapidly nowadays. The existing of many e-commerce website helped customer to make a business transaction through online. Buying and purchasing goods become easier through an online shopping or e-commerce. User just need to click the product they want and the company will process the purchase from the customer and deliver the product right in front of the door within a period of time. However, the growths of many e-commerce website do not accompanied by the quality of the website itself Due to that, e-commerce website should be measure and focus on its quality especially the functionality of the website in order to meet the standard and satisfied user need.